Interaction of Socio-demographic Characteristics on Acceptance of Disability Among Individuals With Physical Disabilities - Park, Eun-Young; Kim, Jung-Hee (Frontiers in Psychiatry, 2021)
This study aimed to investigate the interaction of sociodemographic characteristics on acceptance of disability among individuals with physical disabilities (IWPD). Data from the 8th Panel Survey of Employment for the Disabled in Korea (PSED) in the second wave were used. A sample concerning the first phase of disability was extracted using the one-step colony method to extract regions and was stratified based on the type of disability, disability grade, and age. To explore the association between acceptance of sociodemographic characteristics and of disability, we used a general linear model. A significant main effect was observed in employment, health status, degree of help, and subjective economic status. Regarding employment status, acceptance of disability in unemployment of IWPD with less than high school was lower as compared to those with more than high school. We observed that unemployed IWPD with low income or poor health status could be the group with the highest risk for acceptance of disability. Individuals in the low economic group were more religious than those in the high economic one. These findings indicate that specialized intervention programs that consider religion, economic status, employment, education, health, and their interactions would be effective for acceptance of disability. Interdisciplinary team members should consider the individual profiles of these populations and implement suitable support and rehabilitation programs.